Reactive Nanoparticles Derived from Polysaccharide Phenyl Carbonates - Martin Gericke; Katja Geitel; Cornelia Jörke; Joachim H. Clement; Thomas Heinze (Molecules, 2021)
Polysaccharide (PS) based nanoparticles (NP) are of great interest for biomedical applications. A key challenge in this regard is the functionalization of these nanomaterials. The aim of the present work was the development of reactive PS-NP that can be coupled with an amino group containing compounds under mild aqueous conditions. A series of cellulose phenyl carbonates (CPC) and xylan phenyl carbonates (XPC) with variable degrees of substitution (DS) was obtained by homogeneous synthesis. The preparation of PS-NP by self-assembling of these hydrophobic derivatives was studied comprehensively. While CPC mostly formed macroscopic aggregates, XPC formed well-defined spherical NP with diameters around 100 to 200 nm that showed a pronounced long-term stability in water against both particle aggregation as well as cleavage of phenyl carbonate moieties. Using an amino group functionalized dye it was demonstrated that the novel XPC-NP are reactive towards amines. A simple coupling procedure was established that enables direct functionalization of the reactive NP in an aqueous dispersion. Finally, it was demonstrated that dye functionalized XPC-NP are non-cytotoxic and can be employed in advanced biomedical applications.